AZOLLA AND DUCKWEED PYROLYSIS PROCESS TO BECOME ENVIRONMENTALLY FRIENDLY FUEL - Kamal, Dianta Mustofa; Syuriadi, Adi; Gunadi, Gun Gun R; Heryana, Ghany (Jurnal Ilmiah Teknologi dan Rekayasa, 2025)
Pyrolysis is a thermochemical conversion process carried out to efficiently convert biomass, such as azolla and duckweed, to produce environmentally friendly fuels. This study aims to compare the results of the pyrolysis process of azolla waste with duckweed into fuel. This study uses a pyrolysis reactor to produce fuel products whose main products are syngas, bio-oil, and environmentally friendly carbon charcoal. From this study, it was found that azolla only produces 0.6% oil. This is 2.07% lower than duckweed, so duckweed is a potential raw material for bio-oil. On the other hand, azolla is able to produce more syn-gas fuel than duckweed, as evidenced by the longer ignition of azolla than duckweed.